Prorogation by submission under art. 26 of Brussels Ibis Regulation and the protection of weaker parties - Lima Pinheiro, Luís de (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Section 7 of Chapter II of the Brussels Ibis Regulation deals with prorogation of juris-diction. The choice of jurisdiction can be made by a choice-of-court agreement or by a trust provision (Art. 25), or by submission to the court seized (Art. 26). The purpose of Art. 26 is, in part, common to the purpose of Art. 25: to respect freedom of choice. However, where one of the parties is a typically weaker party, it may be appropriate to limit freedom of choice or, as it is the case in Art. 26(2), to provide for a duty of information aimed at overcoming the information asymmetry between the parties. The present essay addresses the main interpretation and gap filling issues arising therefrom.